Surgical obturator of upper jaw post hemi-maxillectomy sinonasal cancer - Debby Saputera; Hamita; Tri Nurrahman; Ita Amelia Fransiska; Hengki Robiyansyah (Indonesia Prosthodontic Association, 2023)
Surgical obturator is a maxillofacial prosthesis used in post-hemimaxillectomy patients to close defects and main-tain the integrity of components presents in the oral and nasal cavities due to sinonasal cancer. Maxillary defects in maxillofacial patients will lead to stomatognathic disorders and loss of confidence. Prosthetic rehabilitation is an im-portant procedure in palate reconstruction after sinonasal cancer surgery, include forms of treatment carried out in multidisciplinary cooperation with the ear, nose and throat, surgical oncology, oral surgery, and prosthodontics. This article provides information on post-hemimaxillectomy patient management with a surgical obturator. A 65-year-old female patient came to the prosthodontist of Gusti Hasan Aman Banjarmasin Dental and Oral Hospital, on referral from the Banjarmasin Alert Surgery Special Hospital with a diagnosis of sinonasal cancer with hemimaxillectomy and palate reconstruction. Before the operation, impression is carried out first on the maxillary area using algi-nate. The obturator shape is created by optimizing the retention of the remaining anatomical structures, creating de-signs on the model, creating clasp retention using wire 0.8, processing with acrylic, followed by postoperative obtu-rator insertion. It is concluded that surgical obturator can be used as post hemimaxillectomy rehabilitation.